Os santos de casa: um estudo sobre família, comunidade e religião no menor município brasileiro = The house saints : a study on family, community and religion in the smallest Brazilian municipality - Machado, Carlos Eduardo (Ciencias sociales y religión, 2013)
The transformations of the Brazilian religious field affect the other fields of social life. In addition to the public sphere that starts to experience more plural manifestations and contacts, private spaces and family nuclei also feel the impacts of this movement. In this way, not only does the religious field change, but the religious practices themselves and the relationships between individuals of different religious backgrounds are changed. Based on these considerations, I present in this article some reflections originated from the research carried out in the city of Borá, in the interior of the State of São Paulo, Brazil. Known as the smallest Brazilian city in terms of population, Borá has unique characteristics in its formation. The relations between the people of Bora are either parental or very close, the families that first arrived in the region constituted a community structure with Catholic characteristics present until today. With the recent transformations that affect the social and economic field, adding to the growth of Protestant churches in the municipality, Borá provides a contemporary portrait of the internal changes in the Brazilian religious field, and how the notions of family and community are present as mediators in this new context.